The sectoral effects of monetary policy in Hungary: A structural factor analysis - Gábor Pellényi (Magyar Nemzeti Bank, 2012)
This paper uses a structural factor model to analyze sectoral heterogeneity in the impact of monetary policy in Hungary. Monetary shocks are identified with sign restrictions. The impulse responses of aggregate variables are similar to the findings of previous VAR based studies. The sectoral responses reveal considerable heterogeneity. In particular, sectors more reliant on external finance show larger output responses, while healthier corporate balance sheets imply weaker price responses. These results suggest that the credit channel of monetary transmission is operating in Hungary as well. In addition, there appears some role for the interest sensitivity of demand and price rigidities in explaining the heterogeneity of sectoral responses.
Keywords: C32; E32; E52; 330; structural factor model; monetary policy; credit channel; sectoral heterogeneity